Analysis of the potential and effectiveness of local revenue receipts at the livestock and animal health service office in Mimika Regency - Meilani, Raden Roro Ingesti; Urip, Transna Putra; Mollet, Ary (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the potential and effectiveness of Local Own-Source Revenue (PAD) from the Livestock and Animal Health Service Office in Mimika Regency from 2017 to 2024. It also seeks to identify strategic efforts to optimize PAD contribution from the livestock sector, particularly through retribution on slaughterhouse services, animal health services, and livestock production. Research/methodology: A mixed-method approach was applied, combining quantitative descriptive analysis with qualitative insights. Data were sourced from secondary documents and field observations. The study used potential analysis, effectiveness ratio calculations, and SWOT analysis to examine income realization and improvement strategies. Results: The findings reveal that PAD from the Livestock and Animal Health Service has strong potential, especially in pig slaughterhouses (RPB), UPTD breeding units, and Puskeswan. Effectiveness levels often exceed 100%, indicating very effective performance, though certain units such as RPH-U remain underutilized. The retribution potential is not yet fully maximized due to limited public awareness, regulatory gaps, and infrastructural constraints. Conclusions: The livestock sector significantly contributes to regional income and holds untapped potential. With better regulatory support, infrastructure improvements, and digital system development, PAD from this sector can be further optimized. Strategic planning is essential for sustaining these gains. Limitations: This study is limited by the availability of consistent field data and affected by external factors such as disease outbreaks (e.g., ASF). Contribution: The research provides practical recommendations for local governments to enhance fiscal independence through livestock-based revenue streams and contributes a replicable framework for analyzing PAD potential and effectiveness.